PERSEPSI PELANGGAN TENTANG KUALITAS PRODUK DI UD. WIN-WIN BAKERY - Idam Ardiansyah Ibrahim; Wiliam I. S Mooduto (LP2M Universitas Bina Mandiri Gorontalo, 2023)
The purpose of this study was to see how customers perceive product quality at UD. WIN-WIN bakery in Boalemo Regency. This research is a descriptive type of research with a qualitative research approach. This research is a type of research that tries to describe an event that is happening right now, this research focuses on real problems because it is the point where the exploration occurs. There are 4 indicators that affect customer perceptions of product quality: Individual Need that society in terms of individual needs is quite high. they prefer to consume Win-Win Bakery bread compared to other foods, and most of the sources of information obtained through word of mouth are from family and close friends. Their opinion about the quality of Win-Win Bakery's bread products is very good, the taste is just right, delicious and the price of Win-Win Bakery's bread is very cheap. making win-win bakery bread a recommendation for substitute food in carrying out activities or other activities. And while the external communication (communication with external parties) is that the public knows or knows Win-Win Bakery bakery products from their friends and family, and they enjoy packaging Win-Win Bakery bread packaging that is not easily damaged, according to the Win-Win Bakery community. already has high quality and quality even so the price is still cheap.